Antarctic policymaking & science in the Netherlands, Belgium and Germany (1957-1990) - Abbink, Benjamin Peter (Circumpolar studies, 2009)
The central questions of this research are the following: What was the Antarctic policy of the Netherlands from the late 1950s until 1990? What were its motives, goals, means and effects? What were the roles of the government, the scientific community, non-governmental organisations and possible other actors in this policy? How can these be explained?The focus of this study is on Dutch Antarctic policy. In order to explain Dutch Antarctic policy from the late 1950s until 1990 and to place it in a broader context, Dutch policy will be compared with the Antarctic policies of Belgium and Germany.